Proposed marketing strategy to strengthen adelaide’s brand - Rahmad, Revina; Inggriantara, Alibasjah (The Indonesian Journal of Business Administration, 2019)
Abstract- The competitive in fashion industry is evolving and become more tight. The large number of players in the industry resulting players offer similar value and products. It would be difficult for the players if they do not have amenity that differentiate it with competitors. Adelaide is a form of creativity in fashion industry that offers semi-formal apparel for women. Along with the growth of fashion wear and technology, Adelaide has plan expanding their business activities to gain more market and boost sales. To achieve the goal, Adelaide needs strategy that helps Adelaide strengthening on Marketing and differentiate Adelaide with competitors. The purpose of this research is to find solutions and develop the best marketing strategy that can be implemented to Adelaide.  The strategy formulation process is done by analyzing the external and internal factors that affects Adelaide’s business activity. The results are analyzed and porter’s generic strategy is used as a framework to define strategies. The result of the analysis shows that Adelaide must perform differentiation strategy to achieve competitive advantage. For strengthening Adelaide’s brand, online surveys were given to customers and the results were being analyzed to find the best strategy that can help Adelaide to strengthening its brand. In conclusion, Adelaide has to create uniqueness through differentiation strategy based on product, price, place and promotion. Additionally, strengthening Adelaide’s brand must done by product development and revitalization brand in order to survive in fashion industry and boost its sales. Keywords: Marketing Strategy, Fashion, Brand, Strategic Differentiation, Business Model Canvas